Influence of Elliptic Bore and Non-Newtonian Rheology of Lubricant on the Performance and Stability of Journal Bearing. (2016) - Rahmani, F.; Pandey, R.K.; Dutt, J.K.
Abstract: The objective of this paper is to present investigations related to the performance of fluid film journal bearings incorporating the synergistic effects of elliptic bore and non-Newtonian rheology of lubricant. The Rabinowitsch fluid model has been employed herein for simulating the non-Newtonian rheology of lubricant and Reynolds equation is developed accordingly. The performance parameters (load carrying capacity, coefficient of friction, and stability) of bearing have been investigated and discussed herein in terms of ellipticity (of bearing bore) and non-linearity parameter (relating the non-Newtonian rheology). The combined effects of shear thinning of the lubricant and increase in the ellipticity of the bearing bore cause reduction in the load carrying capacity and increase in friction coefficient in comparison to plain circular bore journal bearing lubricated with Newtonian lubricant. However, increase in the ellipticity of bore alone enhances the stability of the rotor-bearing system.